2021
DOI: 10.3389/fimmu.2021.698697
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of Shrimp Tcf by a Viral Protein Kinase WSV083 Suppresses Its Antiviral Effect

Abstract: Nuclear DNA-binding TCF proteins, which act as the main downstream effectors of Wnt signaling, are essential for the regulation of cell fate and innate immunity. However, their role during viral infection in shrimp remains unknown. Herein, we demonstrated that Litopenaeus vannamei TCF (LvTcf) acts independently of Lvβ-catenin to promote interferon-like protein LvVago1 production, thus mounting the response to WSSV infection. Further, we observed that WSV083, a WSSV serine/threonine protein kinase, bound to LvT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…WSV083, as a serine/threonine-protein kinase, inhibited cell adhesion by attenuating the phosphorylation of the shrimp Focal adhesion kinase (FAK) [ 16 ]. A recent study reported that WSV083 could also bind and phosphorylate shrimp T -cell factor (Tcf), which led to Tcf degradation via the ubiquitin-proteasome pathway and consequently inhibited the Tcf-mediated antiviral effect [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…WSV083, as a serine/threonine-protein kinase, inhibited cell adhesion by attenuating the phosphorylation of the shrimp Focal adhesion kinase (FAK) [ 16 ]. A recent study reported that WSV083 could also bind and phosphorylate shrimp T -cell factor (Tcf), which led to Tcf degradation via the ubiquitin-proteasome pathway and consequently inhibited the Tcf-mediated antiviral effect [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…During WSSV infection in L. vannamei hemocytes , the transcription levels of Lv TCF were increased. However, WSSV produced WSV083 to promote the degradation of Lv TCF via the ubiquitin-proteasome pathway, which suppressed transcription levels of Lv Vago1 46 . Furthermore, Lv IRF, an interferon regulatory factor, regulates the transcription levels of Lv Vago4 and Lv Vago5.…”
Section: Discussionmentioning
confidence: 99%